2012
DOI: 10.3390/s120506415
|View full text |Cite
|
Sign up to set email alerts
|

Road Sign Recognition with Fuzzy Adaptive Pre-Processing Models

Abstract: A road sign recognition system based on adaptive image pre-processing models using two fuzzy inference schemes has been proposed. The first fuzzy inference scheme is to check the changes of the light illumination and rich red color of a frame image by the checking areas. The other is to check the variance of vehicle's speed and angle of steering wheel to select an adaptive size and position of the detection area. The Adaboost classifier was employed to detect the road sign candidates from an image and the supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Its working concept is based on constructing multiple weak classifiers and assembling them into a single strong classifier for the overall task. As indicated in Table 11, the AdaBoost method was used for TSDR in [123,124,125,126,127]. Based on these studies, it can be concluded that the main advantage of the AdaBoost is its simplicity, high prediction power and capability to cascade an architecture for improving the computational efficiency.…”
Section: Traffic Sign Detection Tracking and Classification Methodsmentioning
confidence: 99%
“…Its working concept is based on constructing multiple weak classifiers and assembling them into a single strong classifier for the overall task. As indicated in Table 11, the AdaBoost method was used for TSDR in [123,124,125,126,127]. Based on these studies, it can be concluded that the main advantage of the AdaBoost is its simplicity, high prediction power and capability to cascade an architecture for improving the computational efficiency.…”
Section: Traffic Sign Detection Tracking and Classification Methodsmentioning
confidence: 99%
“…A study comparing various visual descriptors is present in Russell and Fischaber [25] while Ding et al [26] develop a system for detection and identification using the SURF (speeded-up robust features) [27] algorithm and GPGPU (general-purpose gpu) programming model. In Lin et al [28], there is a hybrid approach based on adaptive image pre-processing models and two fuzzy inference schemes checking light illumination and the red color amount of a frame image.…”
Section: Related Workmentioning
confidence: 99%
“…All researchers are implementing their methods to achieve a common goal [ 25 ]. Some researchers have done the detection [ 26 , 27 , 28 ] part, some are tracking the detection and a few have described effective recognition parts [ 29 , 30 ]. According to Paclík et al [ 31 ], an automated traffic sign detection system was introduced for the first time in Japan in 1984.…”
Section: Related Workmentioning
confidence: 99%